Anxiety, resilience and local conditions: A cross‐cultural investigation in the time of Covid‐19. (27th November 2021) - Moret‐Tatay, Carmen; Murphy, Mike
Abstract : The spread of Covid‐19 is a worldwide phenomenon, unprecedented in modern times. Differences among countries in such matters are of interest as they provide a unique window to understand human behaviour and culture. The aim of this study is to examine cross‐cultural differences in state anxiety, and any moderating role of resilience and social contact. Participants from three countries were recruited: Ireland ( n = 449), Italy ( n = 324) and Spain ( n = 471). While these countries share many characteristics, it was anticipated that their experiences might differ because of pronounced differences in governmental measures and the local severity and history of the pandemic at the time of data collection. Results indicated that: (a) Resilience was negatively related to state anxiety both bivariately and multivariately; (b) number of hours outside per week did not predict state anxiety but was negatively correlated with fear of contagious diseases in the essential workers from the Irish sample; (c) national measures had a moderating role in the relationship between resilience and state anxiety; and (d) social contact, in terms of numbers of written, audio or visual interactions, was not a statistically significant predictor of state anxiety. These results may help to understand the adverse impact on mental health.